Calpain signaling: from biology to therapeutic opportunities in neurodegenerative disorders - Metwally, Elsayed; Al-Abbadi, Hatim A.; Hussain, Tarique; Murtaza, Ghulam; Abdellatif, Ahmed M.; Ahmed, Mahmoud F. (Frontiers in Veterinary Science, 2023)
Neurodegenerative disorders represent a major and growing healthcare challenge globally. Among the numerous molecular pathways implicated in their pathogenesis, calpain signaling has emerged as a crucial player in neuronal dysfunction and cell death. Calpain is a family of calcium-dependent cysteine proteases that is involved in many biological processes, such as signal transduction, cytoskeleton remodeling, and protein turnover. Dysregulation of calpain activation and activity has been associated with several neurodegenerative diseases, including Alzheimer's, Parkinson's, and Huntington's diseases. Understanding the intricate structure of calpains is crucial for unraveling their roles in cellular physiology and their implications in pathology. In addition, the identification of diverse abnormalities in both humans and other animal models with deficiencies in calpain highlights the significant progress made in understanding calpain biology. In this comprehensive review, we delve into the recent roles attributed to calpains and provide an overview of the mechanisms that govern their activity during the progression of neurodegenerative diseases. The possibility of utilizing calpain inhibition as a potential therapeutic approach for treating neuronal dysfunctions in neurodegenerative disorders would be an area of interest in future calpain research.